Simulasi Potensi Luapan Sungai Menggunakan HEC-RAS pada Kondisi Curah Hujan Ekstrem - Roland Sitorus; Alfath Zain; Panti Wahyu Ningsih (Jurnal Konstruksi, 2025)
This study simulates flood potential in the Nunyai River, Bandar Lampung City, using GPM-IMERG satellite rainfall data from 2014–2023. A normal distribution was applied to estimate design rainfall, which was then converted into flood discharge using the rational method. The HEC-RAS 5.0.6 simulation results indicate that five river cross-sections are unable to accommodate Q10–Q100 discharges, leading to overflow on the left, right, or both sides. These findings highlight the need for river normalization and levee reinforcement at vulnerable overflow points.